2015
DOI: 10.1088/0004-6256/149/6/180
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mass Models of Dwarf Galaxies From Little Things

Abstract: We present high-resolution rotation curves and mass models of 26 dwarf galaxies from "Local Irregulars That Trace Luminosity Extremes, The H I Nearby Galaxy Survey" (LITTLE THINGS). LITTLE THINGS is a high-resolution (∼6″ angular; <2.6 km s −1 velocity resolution) Very Large Array H I survey for nearby dwarf galaxies in the local volume within 11 Mpc. The high-resolution H I observations enable us to derive reliable rotation curves of the sample galaxies in a homogeneous and consistent manner. The rotation cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
510
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(558 citation statements)
references
References 111 publications
32
510
0
Order By: Relevance
“…The transfer of energy from gas outflows/inflows to collisionless particles is well-studied in the context of the "core-cusp" (Moore 1994;Oh et al 2015) and related "too-bigto-fail" (Boylan- Kolchin et al 2011;Jiang & van den Bosch 2015) problems, which express the discrepancy between the steep central density profiles ("cusps") predicted by ΛCDM models and and the flatter density profiles ("cores") observed in many nearby low-mass galaxies. Recently, a number of studies (for example, Read & Gilmore 2005;Governato et al 2012;Di Cintio et al 2014;Chan et al 2015;Oñorbe et al 2015) have shown that including stellar feedback in simulations can significantly alter dwarf galaxies' density profiles, removing dark matter from the central regions and potentially reconciling the predictions of ΛCDM models with observations, at least for galaxies with M star =10 7−9.6 M e (M halo ≈10 10−11.5 M e ).…”
Section: Relation To Dark Matter Core-creationmentioning
confidence: 99%
“…The transfer of energy from gas outflows/inflows to collisionless particles is well-studied in the context of the "core-cusp" (Moore 1994;Oh et al 2015) and related "too-bigto-fail" (Boylan- Kolchin et al 2011;Jiang & van den Bosch 2015) problems, which express the discrepancy between the steep central density profiles ("cusps") predicted by ΛCDM models and and the flatter density profiles ("cores") observed in many nearby low-mass galaxies. Recently, a number of studies (for example, Read & Gilmore 2005;Governato et al 2012;Di Cintio et al 2014;Chan et al 2015;Oñorbe et al 2015) have shown that including stellar feedback in simulations can significantly alter dwarf galaxies' density profiles, removing dark matter from the central regions and potentially reconciling the predictions of ΛCDM models with observations, at least for galaxies with M star =10 7−9.6 M e (M halo ≈10 10−11.5 M e ).…”
Section: Relation To Dark Matter Core-creationmentioning
confidence: 99%
“…Recognizing current uncertainties in the dark matter density profiles of low-mass galaxies (e.g. Moore 1994;de Blok et al 2001;Boylan-Kolchin, Bullock & Kaplinghat 2011, 2012, we also employ mass profiles derived from dynamical modeling of the observed HI kinematics for a subset of our systems, including NFW fits to the THINGS and Little THINGS samples from de Blok et al (2008) and Oh et al (2015) as well as fits to a Burkert profile (Burkert 1995) from Pace (2016).…”
Section: Estimating σGas(r) and M (R)mentioning
confidence: 99%
“…In particular, we utilize the NFW fits to the THINGS and Little THINGS velocity fields from de Blok et al (2008) Oh et al 2015) and to a Burkert profile (Pace 2016). As in Fig.…”
Section: Dependence On M (R)mentioning
confidence: 99%
“…While the 50% criterion might seem the most sensible and representative, we note that collapse redshift refers to the halo while the SFH refers to the baryons. Since it is conceivable that the baryonic component of the galaxy assembles in the inner region of the subhalo, and since even present-day field dwarf galaxies appear to reside within a few percent of the virial radius of the halo (e.g., Oh et al 2015), it is equally reasonable to argue in favor of the 4% criterion as more representative because most of the halo mass can be gathered later than the assembly of the baryonic galaxy.…”
Section: Constraining 2-3 Kev Wdm Models: the Sf Histories Of Mw Ultrmentioning
confidence: 99%